Numerical Study of Centrifugal Fan with Slots in Blade Surface. (2015) - Rong, Rui; Cui, Ke; Li, Zijun; Wu, Zhengren
Abstract: When the airfoil is working, the geometry of the channel that the fluid flows through changes with the airfoil profile. It makes the magnitude and direction of the velocity change, and resulting in flow separation. The impact produced by flow separation causes the loss of the flow's energy. This paper takes the blade of G4-73No.8D centrifugal fan as the research object. The flow and aerodynamic characteristics of the blades under different incidence angles are analyzed and researched by means of CFD. The slotted technique on centrifugal fan blade with slots cut along the blades pressure side to suction side is adopted. And slotted blade models data are compared with generic models. The results show that the method to create a slot in blade can control the stall of centrifugal fan flow passage availably. And under the appropriate parameters, slotted model can decrease the blade surface resistance and increase lift force effectively. Slotted model also has a role of control and mitigation of boundary layer separation, improving blade aerodynamic performance observably. The slot plays a similar role as the balancing hole, and make the high pressure low speed fluid flow into low-pressure side where the fluid is accelerated and has no extra energy be consumed. The research shows that slotted technique on centrifugal fan blade is useful to improve the characteristics of blade surface flow field, resulting in significant energy saving.